The Influence of Example Non-Example Learning Model on Pancasila Education Learning Outcomes of Class V Students of UPTD SD Negeri 122384 Pematangsiantar - Pasaribu, Yulika; Panggabean, Eva Saryati; Tobing, Minar Trisnawati Lumban (Lembaga Riset Mutiara Akbar, 2025)
This study aims to determine: The Effect of Example Non-Example Learning Model on Pancasila Education Learning Outcomes of Class V Students of UPTD SD Negeri 122384 Pematangsiantar The type of research used in this study is Quantitative Research. The research design that will be used is experimental, with the form of Pre-Experimental Design with